1997
DOI: 10.1007/bf02766114
|View full text |Cite
|
Sign up to set email alerts
|

Is paternal mitochondrial DNA transferred to the offspring following intracytoplasmic sperm injection?

Abstract: During intracytoplasmic sperm injection (ICSI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…40 We and others have previously been unable to detect significant levels of paternal mtDNA polymorphisms in placenta, even in ICSI where the normal processes governing its elimination might be disrupted. 19,41,42 In the single case report of paternally inherited mtDNA the authors identified mtDNA recombinants using PCR analysis of muscle mtDNA. 43 If this were a common occurrence that involved the germline it should be evident in population studies, and currently there is little or no clear evidence that this is the case.…”
Section: Discussionmentioning
confidence: 99%
“…40 We and others have previously been unable to detect significant levels of paternal mtDNA polymorphisms in placenta, even in ICSI where the normal processes governing its elimination might be disrupted. 19,41,42 In the single case report of paternally inherited mtDNA the authors identified mtDNA recombinants using PCR analysis of muscle mtDNA. 43 If this were a common occurrence that involved the germline it should be evident in population studies, and currently there is little or no clear evidence that this is the case.…”
Section: Discussionmentioning
confidence: 99%
“…Such delay could hinder the degradation of the sperm mitochondria and facilitate the persistence of the sperm mtDNA, heteroplasmy, in the embryonic cytoplasm. So far, the completed studies of human ICSI embryos ruled out heteroplasmy (Danan et al, 1999;Houshmand et al, 1997). However, oocytes deficient in their ability to reduce/unmask the sperm mitochondrial capsule could be generated from superficially stimulated cycles and subsequently fail to expose the ubiquitin tag in the sperm mitochondrial membranes.…”
Section: Clinical Considerations: Infertility Diagnostics Vasectomymentioning
confidence: 99%
“…Paternal inheritance has never been observed in humans, either in pedigree studies (Jazin et al 1998;Parsons et al 1997;Sigurdardottir et al 2000;Soodyall et al 1997), or in cases of artificial fertilization using intracytoplasmic sperm injection (ICSI) (Danan et al 1994;Houshmand et al 1997;Torroni et al 1998). However, the numbers of cases that have been examined is small; only 38 ICSI cases have been investigated, and the total number of generational events considered in pedigrees probably does not exceed 2500, even if all the pedigrees used to establish maternal inheritance of various genetic diseases are taken into account.…”
Section: Paternal Leakagementioning
confidence: 99%